Pelatihan Penanganan Penyakit Busuk Buah Kakao serta Manajemen Pemasaran dan Keuangan dalam Rangka Pemberdayaan Kelompok Tani Kakao - Khairad, Fastabiqul; Qolby, Friskia Hanatul; Putra, Vicka Pramudya (Universitas Medan Area, 2024)
This Community Service Program (PKM) collaborated with the Pincuran Ruyuang Farmers Group, which focuses on cacao cultivation and is located in Nagari Solok Bio-Bio, Harau District, Lima Puluh Kota Regency. The main issue in cacao farming production is phytophthora fruit rot, while the management problems include marketing and financial management of the cacao farm. This program's focus was to provide farmer group members with training to address these issues. Several activities were conducted, including community outreach, Good Agricultural Practices (GAP) training for cacao, marketing management training, fruit rot disease control, and liming and fertilization training. The training results showed an 85.48% increase in partners' understanding of GAP and an 83.33% increase in GAP application. Additionally, a reduction in fruit rot disease was observed during the PKM activities. Partners' understanding of marketing and financial management also improved by 85.50%. This increased knowledge is hoped to enable partners to implement better marketing strategies, leading to higher sales and profits.